Managerial efficiency and failure of U.S. commercial banks during the 2007-2009 financial crisis: was this time different? (2016)
Compared with previous crises few banks failed as a result of the U.S. financial crisis of 2007-2009. We investigate the role played by managerial efficiency in the non-systemic bank failures during the crisis. During previous waves of bank failures, cost-inefficient banks and banks with relatively less capital or low-quality assets were more likely to fail. Using data from 2001 to 2010, we show that profit inefficiency—our proxy for managerial inefficiency— is a robust predictor of bank failures while cost inefficiency is unrelated to them. In addition, capital adequacy lost importance in predicting non-systemic bank failures during the crisis while loan quality remained a strong predictor. Our results suggest that profit efficiency can be an important managerial indicator in monitoring banks.